School Management in the Implementation of the Seven Great Indonesian Children's Habits Movement - Sholikhin, Sholikhin; Perawironegoro, Djamaluddin; Sutarman, Sutarman (Early Publishing, 2025)
This research is motivated by the importance of school management in implementing the Seven Habits of Great Indonesian Children Movement in elementary schools. This movement includes the habits of waking up early, praying, exercising, eating healthy and nutritious food, a love of learning, being social, and going to bed early. Elementary School 4 Bendungan Kulon Progo implements this program as a habit-forming activity to foster students' independence. This study aims to analyze school management in implementing the Seven Habits of Great Indonesian Children Movement at Elementary School 4 Bendungan Kulon Progo. This research used a qualitative approach with a case study approach. Data were obtained through observation, interviews, and documentation with informants consisting of the principal, teachers, students, and parents. The sampling technique used snowball sampling. The data obtained were analyzed qualitatively to gain a comprehensive understanding of program implementation. The results show that school management in implementing the Seven Habits of Great Indonesian Children Movement has progressed through the stages of organization, implementation, and supervision. The principal plays a role in organizing and supervising the program, teachers assist students in implementing activities, and parents support the habit-building process at home. The program is implemented routinely and integrated into students' daily activities, helping to foster discipline and independence.